PENGAWASAN PAKAIAN BEKAS DI KABUPATEN INDRAGIRI HILIR - Wahyudi, Indra; Sadad, Abdul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The Department of Industry and Trade has the task of carrying out regional government affairs based on the principle of autonomy and assistance in the field of Industry and Trade and can be assigned to carry out the authority delegated by the government to the regions in the context of decentralization. Based on the data the researchers got when conducting research at the research location of the Department of Industry and Trade of Indragiri Hilir Regency regarding supervision regarding the prohibition of the sale of used clothing carried out by the Department of Industry and Trade, in the Manullang Supervision model theory, there were three variables that formed the link between Supervision and performance. namely Setting Standards, Conducting Measures of Assessment and Conducting Corrective Action, The research method used in this study is qualitative research. With the technique carried out, namely snow ball sampling, to the key informants in this study. In this writing, the informant was the Head of the Trade Department of the Department of Industry and Trade of Indragiri Hilir Regency, Secretary of the Department of Industry and Trade of Indragiri Hilir Regency. Then analyze the data and manage it. Based on the research and discussion that the researchers carried out in the field, it was found that Second hand Clothing Surveillance in Indragiri Hilir District had not been carried out optimally. This is because various factors that influence Supervision of this Regulation are difficult to carry out optimally.Keywords: Supervision, Used Clothing in Inhil District